TMT-based quantitative proteomics reveals the genetic mechanisms of secondary hair follicle development in fine-wool sheep. - Li-Xia Qiu; Qian Yu; Hua-Qian Zhou; Wen-Hua Fan; Jing-Jing Zheng; Yong-Lin Yang; Wen-Zhe Zhang; Xin Cao; Hua Yang (PLoS ONE)
The development of secondary hair follicles influences the quality of sheep wool. However, the mechanism by which proteins mediate the fetal development of secondary hair follicles remains unknown. In this study, the histomorphology of secondary hair follicles was analyzed over four stages of fetal development (75, 85, 95, and 105 gestational days). TMT-based quantitative proteomics was used to compare the differential protein profiles of skin tissues between consecutive developmental periods (75 versus 85, 85 versus 95, and 95 versus 105 gestational days). We found that the density of secondary hair follicles and the secondary hair follicles/primary hair follicles ratio increased from 85 to 105 gestational days. Bioinformatic analysis identified 238, 35, and 348 differentially expressed proteins in the respective comparison periods. Focal adhesion, ECM-receptor interaction, and the estrogen signaling pathway all played important roles in secondary hair follicle development. COL1A1, THBS3, ITGA6, COL6A1, and THBS4 were identified as potential candidate proteins in the initiation of secondary hair follicles. This study provides valuable proteomics data on secondary hair follicle development and thus has deepened our understanding of the molecular mechanisms underlying wool quality traits in fine-wool sheep.